The - Zimbardo, Philip G.
In his landmark book, The Time Paradox, internationally known psychologist Philip Zimbardo showed that we can transform the way we think about our past, present, and future to attain greater success in work and in life. Now, in The Time Cure, Zimbardo has teamed with clinicians Richard and Rosemary Sword to reveal a groundbreaking approach that helps those living with post-traumatic stress disorder (PTSD) to shift their time perspectives and move beyond the traumatic past toward a more positive future